Emotionally Intelligent Instructional Leadership : Madrasah Principal’s Strategies in Building a Conducive School Climate for Learning - Zulkarnain; Warlizasusi , Jumira; Harmi , Hendra; Asha , Lukman; Hamengkubuwono (Corolla International Conference, 2025)
This study aims to describe and analyze the emotionally intelligent instructional leadership strategies implemented by the madrasah principal at MAN 2 Lebong in fostering a conducive school climate for learning. The background of this research lies in the critical role of madrasah principals, not only as academic leaders but also as managers of emotional dynamics within a complex school community. In the context of modern education, which is full of challenges, the ability of madrasah principals to understand and manage emotions effectively is a key factor in creating a healthy and productive learning environment. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis. The participants included the madrasah principal, teachers, and educational staff. The findings reveal that the principal of MAN 2 Lebong integrates elements of emotional intelligence such as empathy, emotional regulation, social awareness, and interpersonal relationship skills into instructional leadership practices, including classroom supervision, teacher development, and the reinforcement of a collaborative and reflective learning culture. These strategies significantly contribute to the creation of an open, supportive, and conducive madrasah environment for both teacher development and student growth. The results indicate that emotional intelligence is a critical aspect that should be incorporated into the professional development of madrasah principals. Therefore, this study recommends that future educational leadership training emphasize emotional and relational dimensions as an integral part of efforts to build a positive and sustainable school climate.